1992
DOI: 10.1128/jb.174.12.4148-4156.1992
|View full text |Cite
|
Sign up to set email alerts
|

Proline biosynthesis in Saccharomyces cerevisiae: molecular analysis of the PRO1 gene, which encodes gamma-glutamyl kinase

Abstract: The PROJ gene of Saccharomyces cerevisiae encodes the 428-amino-acid protein y-glutamyl kinase (ATP:L-glutamate 5-phosphotransferase, EC 2.7.2.11), which catalyzes the first step in proline biosynthesis. Amino acid sequence comparison revealed significant homology between the yeast and Escherichia coli -y-glutamyl kinases throughout their lengths. Four close matches to the consensus sequence for GCN4 protein binding and one close match to the RAP1 protein-binding site were found in the PROJ upstream region. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Surprisingly, PRO1 was repressed by 3AT (Fig. 6A, Pro), consistent with a previous report that PRO1 is not induced by histidine starvation (59). As expected (36), we found that nine of the arginine biosynthetic genes (ARG1, -2, -3, -4, -5, 6, -7, and -8; CPA1; and CPA2) are Gcn4p targets and that most were strongly induced by 3AT (Fig.…”
Section: Fig 3 a Fraction Of Gcn4p Target Genes Is Induced By 3at Isupporting
confidence: 80%
“…Surprisingly, PRO1 was repressed by 3AT (Fig. 6A, Pro), consistent with a previous report that PRO1 is not induced by histidine starvation (59). As expected (36), we found that nine of the arginine biosynthetic genes (ARG1, -2, -3, -4, -5, 6, -7, and -8; CPA1; and CPA2) are Gcn4p targets and that most were strongly induced by 3AT (Fig.…”
Section: Fig 3 a Fraction Of Gcn4p Target Genes Is Induced By 3at Isupporting
confidence: 80%
“…In plants, the first steps of L-proline biosynthesis from L-glutamate are catalyzed by P5C synthetase (an EC number has not been not assigned), a bifunctional enzyme with ␥-GK and ␥-GPR activities (15,44); the ␥-GK activity of the P5C synthetase was also found to be sensitive to L-proline. In contrast, the PRO1 gene of S. cerevisiae was regulated by the general amino acid control system, which increased the expression of many amino acid biosynthetic genes in cells subjected to amino acid starvation conditions (20). However, feedback inhibition of ␥-GK activity remains unknown.…”
Section: Resultsmentioning
confidence: 97%
“…A fragment of the PRO1 gene including the probable TATA box sequences (20) and the tripartite terminator (20) was prepared by PCR performed with genomic DNA from strains MB329-17C and FH515 and oligonucleotide primers 5Ј-ACC CAA GCT TTG GTC AGT GGC ACA G-3Ј and 5Ј-ACC CGA GCT CGA AGG ATT TTA ACG GAT CAC-3Ј (the underlined sequences are the positions of a HindIII site and a SacI site, respectively). The unique 1.8-kb band amplified from genomic DNA of MB329-17C and FH515 was digested with HindIII and SacI and then ligated to the large fragment of pRS415 digested with HindIII and SacI to construct pRS-WTPRO1 and pRS-D154NPRO1, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly in yeast, ? '-glutamyl kinase [31] and ~'-glutamyl phosphate reductase ( [32]; M.C. Brandriss, personal communication) functions are carried by two different proteins.…”
Section: Discussionmentioning
confidence: 99%